Genome-Wide Association Analysis of Boar Semen Traits Based on Computer-Assisted Semen Analysis and Flow Cytometry - Xiyan Yang; Jingkun Nie; Yaxuan Zhang; Suqing Wang; Xiaoping Zhu; Zhili Li; Yunxiang Zhao; Xiuguo Shang (Animals)
Semen quality and persistence are critical for evaluating the usability of individual boars in AI, a standard practice in pig breeding. We conducted GWASs on various semen traits of Duroc boars, including MOT, DEN, ABN, MMP, AIR, and ROS levels. These traits were assessed using FCM and CASA. A total of 1183 Duroc boars were genotyped using the GeneSeek GGP Porcine 50 K SNP BeadChip. The GWAS was performed using three different models: GLM, MLM, and FarmCPU. Additionally, trait heritability was estimated using single- and multiple-trait PBLUP models, yielding 0.19, 0.29, 0.13, 0.18, 0.11, and 0.14 heritability for MOT, DEN, ABN, MMP, AIR, and ROS, respectively. All semen traits exhibited low heritability except ABN, which demonstrated medium heritability. Nine candidate genes (GPX5, AWN, PSP-II, CCDC62, TMEM65, SLC8B1, TRPV4, UBE3B, and SIRT5) were potentially associated with semen traits. These genes are associated with antioxidant and mitochondrial functions in porcine sperm. Our findings provide insight into the genetic architecture of semen traits in Duroc boars, and the identified SNPs and candidate genes may enhance economic outcomes in the pig breeding industry while improving sperm quality through targeted breeding strategies.